Acute effects of running 10km on the medial longitudinal arch height: dynamic evaluation using a three-dimensional motion capture system - Sayo Kuroda (Asociación Española de Ciencias del Deporte, 2024)
In previous studies, static evaluations of changes in the navicular height by long-distance running have shown that the navicular height decreases after long-distance running. However, few studies have performed dynamic evaluations of the changes in the supportive function of the medial longitudinal arch (MLA) height. Therefore, to evaluate the changes in the MLA height of healthy recreational runners before and after running 10 km, we performed static and dynamic evaluations. Nineteen runners underwent MLA height measurements before and after running 10 km on a treadmill. The measurements of MLA height were performed using three-dimensional motion analysis while the participants were barefoot in the sitting, standing, and walking positions. The heel contact value, minimum value, difference between the heal contact and minimum values, dynamic navicular drop (DND) height, and time when the minimum MLA height was reached during the stance phase of gait (timing) were calculated.　After running 10 km, the standing MLA height decreased (18.04-16.86 mm; p<0.05), DND increased (6.32-7.77 mm; p<0.05), and timing was delayed (82.6%-85.2%; p<0.05). The DND, which is a dynamic measure of the MLA support function, increased with long-distance running, thereby decreasing the support function. The degree of deformation of the foot morphology in the terminal stance when the tissues comprising the MLA are stressed may influence injuries.